Role of Auriculotherapy in the Treatment of Temporomandibular Disorders with Anxiety in University Students - Iunes, Denise Hollanda (Evid Based Complement Alternat Med, 2015)
Introduction. The aim of this study was to evaluate the role of auriculotherapy with mustard seeds in the treatment of temporomandibular disorders (TMDs), anxiety, and electromyographic (EMG) activity in university students. Methodology. The State Trait Anxiety Inventory (STAI), Research Diagnostic Criteria (RDC) for TMDs (RDC/TMDs), and electromyography were used in this study of 44 college students with high levels of anxiety and TMDs. The subjects were divided into two groups: an auriculotherapy (AA) group (n = 31) and an AA sham group (n = 13). The mustard seeds were applied to the shenmen, rim, sympathetic, brain stem, and temporomandibular joint (TMJ) points in the AA group and to sham points in the external ear and wrist in the AA sham group. The treatment protocol was 10 sessions (two treatments per week). Results. Anxiety (p < 0.01) was significantly reduced in the AA group. This group also showed a decrease in tender points in the mandibular posterior region (p = 0.04) and in the right side of the submandibular region (p = 0.02). Complaints of bilateral pain were reduced in the temporal tendon (p ≤ 0.01) and in the left side of the ATM (p < 0.01). In addition, electromyographic (EMG) activity was reduced during temporal muscle contraction (p = 0.03).  Conclusion. Auriculotherapy was effective in the treatment of students with anxiety and TMDs.